Disulfiram Enhances the Antineoplastic Activity and Sensitivity of Murine Hepatocellular Carcinoma to 5-FU via Redox Management - Iftekhar Hassan; Hossam Ebaid; Ibrahim M. Alhazza; Jameel Al-Tamimi; Ahmed M. Rady (MDPI AG, 2023)
The efficacy of anticancer drug 5-FU is suppressed due to various factors, including severe side effects and decreased insensitivity during prolonged chemotherapy. Elevated endogenous copper (Cu) levels are one of the prominent hallmark features of cancer cells. In the present investigation, this feature was targeted in diethyl nitrosamine-phenobarbital-induced hepatocellular carcinoma (HCC) in a rat model system by an established anticancer drug, 5-FU, co-administered with copper and its chelating agent, disulfiram. After treatment with the test chemicals in HCC-induced rats, blood and liver samples were subjected to biochemical, molecular, and histopathological analyses. The analysis revealed that reactive oxygen species-mediated oxidative stress is the crucial etiological reason for the pathogenesis of HCC in rats, as evidenced by the significantly compromised activity of major antioxidant enzymes and elevated levels of oxidative damaged products with major histological alterations compared to the control. However, the combination of 5-FU with DSF demonstrated a significant improvement in most of the parameters, followed by 5-FU-Cu in the combination-treated groups. The combination treatment improved the histological details and triggered apoptosis in the cancer cells to a remarkable extent, as the levels of cleaved PARP and caspase-3 were significantly higher than those in the HCC rats treated with the drug alone. The present study envisages that manipulating the Cu-level greatly enhances the antineoplastic activity of 5-FU and sensitizes cancer cells to the increased efficacy of the drug.